ANALISIS KEUNTUNGAN USAHA PETERNAKAN AYAM BROILER POLA KEMITRAAN DENGAN PT CIOMAS ADISATWA DI NAGARI MUARO BODI: PROFIT ANALYSIS OF BROILER CHICKEN FARMING BUSINESS PARTNERSHIP PATTERN WITH PT CIOMAS ADISATWA IN MUARO BODI VILLAGE - Andiprita Andiprita; Maiyontoni Maiyontoni; Rini Elisia; Refika Komala; Fildza Arief Syuhada (Tropical Animal Science, 2026)
The development of the livestock sector is part of the growth of the agricultural industry, as it holds strategic value in meeting food needs. The livestock subsector contributes to agricultural development, with the poultry industry being a key driver of business development in the livestock subsector. One interesting business activity to study in the livestock subsector is the broiler chicken business. Broiler chicken farming can be developed through a partnership model, namely a broiler chicken farm implemented using a nucleus-plasma scheme. This study aims to determine the partnership model implemented by Rizaldi Soetra with PT Ciomas Adisatwa and to determine the production costs and profits obtained from Rizaldi Soetra's broiler chicken farm. The study was conducted on Rizaldi Soetra's farm for two months, from June to August 2025 in Muaro Bodi Village, IV Nagari District, Sijunjung Regency. The study used 13,000 broiler chickens owned by Rizaldi Soetra during one production period to determine income and profits. The method used was a survey with direct field observations to obtain the necessary data. Data collection was conducted using observation, interviews, and documentation techniques. The results of this study indicate that Rizaldi Soetra's broiler chicken farm, operating in partnership with PT Ciomas Adisatwa, is highly profitable for farmers. It can be concluded that the partnership between Rizaldi Soetra's broiler chicken farm and its partner company, PT Ciomas Adisatwa, spans from upstream to downstream. The production costs for this business per unit are Rp386,086,758.11, resulting in a profit of Rp53,317,857.89, with a R/C ratio of 1.14.